Domain Wall Displacement is the Origin of Superior Permittivity and Piezoelectricity in BaTiO3 at Intermediate Grain Sizes. (3rd September 2013) - Ghosh, Dipankar; Sakata, Akito; Carter, Jared; Thomas, Pam A.; Han, Hyuksu; Nino, Juan C.; Jones, Jacob L.
<x xml:space="preserve">Abstract</x> The dielectric and piezoelectric properties of ferroelectric polycrystalline materials have long been known to be strong functions of grain size and extrinsic effects such as domain wall motion. In BaTiO3, for example, it has been observed for several decades that the piezoelectric and dielectric properties are maximized at intermediate grain sizes (≈1 μm) and different theoretical models have been introduced to describe the physical origin of this effect. Here, using in situ, high‐energy X‐ray diffraction during application of electric fields, it is shown that 90° domain wall motion during both strong (above coercive) and weak (below coercive) electric fields is greatest at these intermediate grain sizes, correlating with the enhanced permittivity and piezoelectric properties observed in BaTiO3. This result validates the long‐standing theory in attributing the size effects in polycrystalline BaTiO3 to domain wall displacement. It is now empirically established that a doubling or more in the piezoelectric and dielectric properties of polycrystalline ferroelectric materials can be achieved through domain wall displacement effects; such mechanisms are suggested for use in the design of new ferroelectric materials with enhanced properties.